Formulation and Characterization of Chitosan Microparticulate System Using Central Composite Design for the Drug: Lafutidine - Kumar, Sunil; Goyal, Naveen (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: To formulate a Micro particulate system using central composite design to remain in the stomach for prolonged time and used for Gastroretentive drug delivery. Materials and Methods: Gastroretentive Microspheres were prepared by Emulsion Solvent Evaporation. Micro particulate system were evaluated for micro meritic study, percentage yield, drug entrapment efficiency, in-vitro buoyancy, surface morphology, in-vitro drug release, in-vivo floating study and stability studies. Results: The micro meritic parameters of floating microspheres were found to be within the acceptable limits. The particle size of microspheres was found to be in the range 3.43–15.38 μm. The entrapment efficiency was found to be in the range of 72.02–95.02%. The floating microspheres were spherical in shape with distinct pores, slightly rough surface when observed under scanning electron microscopy. The percentage yield was found to be in the range of 68–89%. The in-vitro buoyancy was found to be in the range of 55.67–92.55% and a total buoyancy time of more than 10 h. The in-vitro dissolution studies showed a cumulative % release in the range of 77.67–95.41%. The optimized formulation F4 was floating in rat stomach for almost 8 h. All the formulations followed Korsemeyer- Peppas kinetics indicating drug release by non-fickian release mechanism. The stability studies showed that floating microspheres were stable at 40 ± 2°C. Conclusion: The optimized formulation showed good floating for 12 h in stomach of rat. The formulation was able to treat the alcohol induced ulcer and also found good stability.
Keywords: Lafutidine; Chitosan; Central composite design; In vitro drug release; Microparticulate system